2018
DOI: 10.1016/j.scriptamat.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Achieving ultra-high hardness of nanostructured Mg-8.2Gd-3.2Y-1.0Zn-0.4Zr alloy produced by a combination of high pressure torsion and ageing treatment

Abstract: A Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr(wt.%) alloy is subjected to a series of thermal and mechanical treatments involving solution treatment, artificial ageing to peak hardness, high pressure torsion (HPT) and a second artificial ageing. During HPT precipitates dissolve and during the final post-HPT ageing, the supersaturated solid solution decomposes and solutes segregate at grain boundaries. By employing this T6+HPT+T5 treatment, the hardness increases to 156±1 HV, which is much higher than that achieved by any other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(14 citation statements)
references
References 38 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Thus, ageing treatment at 200 • C for 24 h of a sample with six ECAP passes results in an increase of 40% of the mechanical strength compared with the material in the as-extruded condition, (from 325 MPa to 456 MPa). Several reinforcing mechanisms have been proposed to explain the increase in the mechanical strength of Mg-Gd-RE-Zn alloys [4][5][6][7][8][9][10][11][12][13], such as grain size refinement, LPSO phase, solid solution, precipitation, dislocation, and nanoscale segregation. Unfortunately, all these parameters change differently during the ECAP processing, and it is not possible to carry out a systematic study to isolate each contribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, ageing treatment at 200 • C for 24 h of a sample with six ECAP passes results in an increase of 40% of the mechanical strength compared with the material in the as-extruded condition, (from 325 MPa to 456 MPa). Several reinforcing mechanisms have been proposed to explain the increase in the mechanical strength of Mg-Gd-RE-Zn alloys [4][5][6][7][8][9][10][11][12][13], such as grain size refinement, LPSO phase, solid solution, precipitation, dislocation, and nanoscale segregation. Unfortunately, all these parameters change differently during the ECAP processing, and it is not possible to carry out a systematic study to isolate each contribution.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, during ECAP processing, the partial dissolution of the LPSO phase could occur and solute atoms could segregate, during the thermal treatment at 200 • C, in those defects generated during ECAP, such as vacancies or dislocations. Sun et al [12,13] have demonstrated, using high-angle annular dark-field scanning TEM, the segregation along the grain boundaries of Gd, Y, and Zn atoms during HPT in this alloy. The use of a combination process based on a T6 + HPT + T5 treatment in a similar alloy induces the highest hardness.…”
Section: Precipitation Of Prismatic Platesmentioning
confidence: 91%
See 1 more Smart Citation
“…Table 4 lists the tensile properties of some Mg alloys treated by HPT. Notably, some Mg alloys treated by HPT [107][108][109][110][111][112] show nanoscale grains and high microhardness; however, their tensile properties are not determined probably because of the small size of the HPT samples. Zheng et al [106] fabricated an ultrafine-grained Mg-Zn-Zr-Ca alloy (0.77 µm) via HPT + subsequent annealing and achieved the simultaneous improvement of strength and ductility (YS = 235 MPa, UTS = 328 MPa, elongation = 26.1%), which can be ascribed to GB strengthening and sufficient strain-hardening capability regained by recrystallization.…”
Section: Severe Plastic Deformation Technologiesmentioning
confidence: 99%
“…Zheng et al [106] fabricated an ultrafine-grained Mg-Zn-Zr-Ca alloy (0.77 µm) via HPT + subsequent annealing and achieved the simultaneous improvement of strength and ductility (YS = 235 MPa, UTS = 328 MPa, elongation = 26.1%), which can be ascribed to GB strengthening and sufficient strain-hardening capability regained by recrystallization. Sun et al [110][111][112] conducted a series of treatments on Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr alloy, including solution treatment, artificial aging, HPT, and second artificial aging (i.e., T6 + HPT + T5). The samples treated by T6 + HPT + T5 show the nanograined structure with the average grain size of (35 ± 2) nm (Figs.…”
Section: Severe Plastic Deformation Technologiesmentioning
confidence: 99%